2015
DOI: 10.1016/j.brq.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Board composition and performance in Spanish non-listed family firms: The influence of type of directors and CEO duality

Abstract: This study analyzes the effect that certain characteristics of board of directors in Spanish non-listed family firms have on performance. The results of a hierarchical regression analysis on a database of 544 firms show a negative effect of a higher proportion of executive directors and a positive effect of CEO duality. No effects were found in relation to the diversity of family directors (executive or non-executive). In relation to the effect of outside boards, the influence on performance is negative except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 100 publications
(228 reference statements)
0
37
1
2
Order By: Relevance
“…• Age of the company (Ln(Age)): Measured as the number of years since the founding of the company, we took the natural logarithm of age in order to minimize asymmetry, given the high level of variability found in this variable. The inclusion of age as a control variable is common in the literature (Andres, 2014;Arosa et al, 2010;Cabrera-Suárez & Martín-Santana, 2015). It is seen as a measure of a company's ability to compete in a highly competitive environment.…”
Section: • Control Variablesmentioning
confidence: 99%
“…• Age of the company (Ln(Age)): Measured as the number of years since the founding of the company, we took the natural logarithm of age in order to minimize asymmetry, given the high level of variability found in this variable. The inclusion of age as a control variable is common in the literature (Andres, 2014;Arosa et al, 2010;Cabrera-Suárez & Martín-Santana, 2015). It is seen as a measure of a company's ability to compete in a highly competitive environment.…”
Section: • Control Variablesmentioning
confidence: 99%
“…Furthermore, [91] examined the performance of 200 firms that had either switched away from or switched to CEO duality, and found significantly lower returns for the firms without CEO duality. In [92], the authors examined the Spanish non-listed family firms, and the results showed a positive response when the same person held top positions in the BOD and management. On the other hand, [88] examined the relation between Initial Public Offering (IPO) underpricing, CEO duality, and strategic ownership in 12 Arab countries of the Middle East and North Africa (MENA) region, and showed that underpricing increases with CEO duality.…”
Section: Ceo Duality Accounting Expertise Of Fqds and Corporate Sustmentioning
confidence: 99%
“…The multiple effects of shareholder ownership concentration lead to popularity of this topic among scholars and practitioners. Researchers typically analyse the relationship between shareholder equity concentration and corporate financial performance, borrowing rates and profitability (Barinov, 2017;Feng et al, 2016;Leung et al, 2014;Cabrera-Suarez & Martin-Santana, 2014;Manzaneque et al, 2016). Nevertheless, a lack of the research into the interaction between ownership concentration and corporate market risks is still observed.…”
Section: Introductionmentioning
confidence: 99%